Association Between 6-Minute Walk Test and All-Cause Mortality, Coronary Heart Disease–Specific Mortality, and Incident Coronary Heart Disease. (June 2014) - Yazdanyar, Ali; Aziz, Michael M.; Enright, Paul L.; Edmundowicz, Daniel; Boudreau, Robert; Sutton-Tyrell, Kim; Kuller, Lewis; Newman, Anne B.
Objective: To examine the association between 6-min walk test (6 MWT) performance and all-cause mortality, coronary heart disease mortality, and incident coronary heart disease in older adults.Method: We conducted a time-to-event analysis of 1, 665 Cardiovascular Health Study participants without prevalent cardiovascular disease with a 6 MWT.Results: During a mean follow-up of 8 years, there were 305 incident coronary heart disease events, and 504 deaths of which 100 were coronary heart disease–related deaths. The 6 MWT performance in the shortest two distance quintiles was associated with increased risk of all-cause mortality (290-338 m: hazard ratio [HR] = 1.7; 95% confidence interval [CI] = [1.2, 2.5]; <290 m: HR = 2.1; 95% CI = [1.4, 3.0]). The adjusted risk of coronary heart disease mortality incident events among those with a 6 MWT < 290 m was not significant.Discussion: Performance on the 6 MWT is independently associated with all-cause mortality and is of prognostic utility in community-dwelling older adults.